Features of refractive therapy and functional methods in the treatment of progressive myopia in children - Tsybulskaya, T. E. (Zaporozhye Medical Journal, 2016)
The progressive increase in the incidence of myopia in children makes it an important object of research in medical practice. Aim. With the aim of clinical evaluation of the efficiency of the impact of refractive therapy and functional methods on myopic refractogenesis we examined 90 patients (180 eyes) with mild myopia. Methods and results. It was revealed that the refractive therapy with orthokeratologic lenses in patients with myopia helps to improve the functional condition of the accommodation apparathus that is expressed in increasing of reserve of relative accommodation on average in 3,8 times, reserve of absolute accommodation on average in 2,8 times, decreasing the familiar tone of accommodation by an average of 0,58 dpt. Functional methods of treatment also has a positive effect on the condition of the accommodation apparatus that is expressed in increasing of reserve of relative accommodation on average in 1,5 times, reserve of absolute accommodation on average in 1,4 times, decreasing the familiar tone of accommodation by an average of 0,34 dpt, but require repeated courses of therapy. In patients on the background of refractive therapy, increasing of clinical refraction was in average 0.21 dpt, the axial eye length in average0.18 mm, in contrast to the group of patients who were passing the functional treatment, in whom increasing of clinical refraction were in average 0.62 dpt, the axial length of the eyeball in average0.42 mmfrom the initial data. Conclusion. Results showed the risk of progression of myopia in children reducing on the background of refractive therapy with orthokeratologic lenses.